Determination of the Beginning of Prayer Time on the Mount Prau Hiking Trail by Applying Spherical Trigonometry - Nur Aulia, Shofinatul Wahdah; Hamid, Abdulloh; Yuliati, Dian; Asyhar, Ahmad Hanif; Khaulasari, Hani (University of Muhammadiyah Sumatera Utara, 2024)
Determining the beginning of prayer time on the Mount Prau hiking trail is very important for Muslims, especially when performing the five daily prayers. Calculation of the beginning of prayer time is important even though prayers can be performed within a certain time range. This study aims to apply spherical trigonometric calculations and to determine the results of the beginning of prayer time on the Mount Prau hiking trail. This research uses spherical trigonometry hisab method with the required data are latitude of place, longitude of place, solar declination and equation of time. The calculation results show the exact prayer time, such as dawn between 04.24 to 04.29 WIB, zuhur between 11.39 to 11.44 WIB, asar between 15.01 to 15.05 WIB, maghrib between 17.32 to 17.36 WIB and isya between 18.46 to 18.51 WIB. This information is useful for climbers of Mount Prau so that they can carry out worship on time.